2019
DOI: 10.1007/s40200-019-00383-5
|View full text |Cite
|
Sign up to set email alerts
|

Sugary beverages are associated with cardiovascular risk factors in diabetic patients

Abstract: Purpose Sugar-sweetened beverages (SSBs) containing high amount of added sugars have increased over the last decades. Due to increased risk of cardiovascular events in type 2 diabetes mellitus (T2DM) patients, we designed a study to assess the association between SSBs and metabolic syndrome, a collection of cardiovascular risk factors, in these patients. Methods A cross-sectional study was performed on T2DM adults (N = 157). Participants had no serious disease or insulin treatment. SSBs records were obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Sin embargo, otros trabajos han mostrado resultados contrarios. Así, un estudio observó que aproximadamente la mitad de los sujetos con DM2 consumieron al menos 150mL por día de bebidas azucaradas 23 , elevando su riesgo cardiovascular. Incluso, se ha reportado un alto consumo de bebidas azucaradas en pacientes con DM2 sin hemodiálisis (49%) y en aquéllos con DM2 y hemodiálisis (47%) en Nueva Zelanda 24 .…”
Section: Comparación Con Otros Estudiosunclassified
“…Sin embargo, otros trabajos han mostrado resultados contrarios. Así, un estudio observó que aproximadamente la mitad de los sujetos con DM2 consumieron al menos 150mL por día de bebidas azucaradas 23 , elevando su riesgo cardiovascular. Incluso, se ha reportado un alto consumo de bebidas azucaradas en pacientes con DM2 sin hemodiálisis (49%) y en aquéllos con DM2 y hemodiálisis (47%) en Nueva Zelanda 24 .…”
Section: Comparación Con Otros Estudiosunclassified
“…In the analysis for patients with specific cardiometabolic diseases, SSBs consumption was associated with a higher risk of CMM in hypertensive patients but not in patients with diabetes and in patients with cardiovascular diseases. A cross-sectional study found a positive association between SSBs intake and hypertension in patients with type 2 diabetes [ 14 ]; however, this study was limited by small sample size ( N = 157) and was not adjusted for medication use. The confounding effects on drug use in the relationship between SSBs consumption and CMM risk might be partly explained by the biological mechanism through which SSBs contribute to cardiometabolic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that each additional cardiometabolic disease may double the risk of mortality [11]. Previous studies have shown that lifestyle behaviours, including smoking and alcohol consumption, are associated with a higher risk of CMM; however, little is known about the role of dietary factors, especially sweet beverages, in disease progression from the single cardiometabolic disease state to CMM state [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…SSB consumption has been proven to be associated with adverse health consequences in both the overall and the diabetic populations. Previous literature has reported that adults with T2DM who consumed more SSBs had an elevated risk of developing numerous adverse health outcomes such as abdominal obesity[ 34 ], cardiovascular diseases[ 35 ], gout[ 36 ], poor cognitive function[ 37 ], and tooth loss[ 34 - 38 ]. Although these studies applied a cross-sectional design using a survey questionnaire, a positive association between SSB intake and risk of adverse health outcomes was identified, which should motivate T2DM patients to reduce SSB intake or stop consuming SSBs altogether to decrease the risk of adverse outcomes.…”
Section: Ssb Consumption In T2dm Patientsmentioning
confidence: 99%